Autonomization of European Ultra-Peripheral Regions (XX—XXI Centuries) - E. O. Muslimova (Научный диалог, 2022)
The issue of the specifics of the “center — regions” relations of the European island regions (Faroe, Aland, Canary, Balearic, Azores, Sicily, Sardinia, Madeira), identified on the basis of ultra-peripheral criteria, is considered. Attention is paid to the formation of a belt of ultra-peripheral regions in the pan-European space. The results of a comparative analysis of the expanding stages of the autonomy of the studied territories are presented. The question is raised about the institutional and constitutional design of the special status of regions. Particular attention is paid to the achieved breadth of autonomous competencies and powers. The novelty of the study is seen in the formulation of the research problem from a new research perspective — the concept of ultraperipherality. The author dwells on the consideration of bilateral relations at several levels of political interaction: the ultraperiphery is the national “center”, the ultraperiphery regions are the EU. The relevance of the study is due to modern political and other processes taking place in the European Union under the influence, including the processes of autonomization of regions and their emergence to a new level of political influence. A classification of regions is proposed according to several criteria related to their autonomy and the acquisition of self-government. It is proved that the expansion of autonomy is one of the components of a special approach to the development of the region and the satisfaction of its needs.